Desenvolvimento de metodologias de avaliação e monitoramento do desgaste no par tribológico RISER/ENRIJECEDOR - Moraes, Monique Alves Franco de (2013)
In this work, methodologies to evaluate the wear of flexible riser pipe and bend stiffener samples were developed. In order to achieve this goal, a three coordinate measuring machine (3CMM) was used to evaluate the wear rates of samples tested in in a large-scale tribometer. Additionally, the events that occur during the sliding wear of these samples were correlated with vibration signals from the tribometer structure. The first methodology was applied to estimate the linear wear of riser samples of the polyamide outer coating that was based on the thickness reduction during the test. The second methodology was designed to estimate the volumetric wear loss of the bendstiffener samples. To evaluate the thickness loss of the riser samples, the Calypso® software was used to define the alignment and to determine and execute the measurement strategy. In order to assess the bend-stiffener volume, the same software was used to define the system alignment. The Dimension Volume® software was used to define and to perform the measurement strategy. The sample volume was calculated using a specially designed program that was developed in Matlab®. In order to analyze the vibrations during the wear test, a routine of data acquisition, monitoring and storage of vibration signals in Labview® software was developed and implemented. The results showed that the developed methodology to quantify the riser thickness loss using a 3CMM is viable and efficient in measuring the wear process of this tribosystem. It was also found that the developed program using Matlab® was an effective tool to evaluate the volumetric losses of bend-stiffeners samples. The measurement strategy using a mesh spacing of 1 mm x 1 mm was considered the most adequate to estimate the volume of a bend-stiffener sample accurately and with the least possible amount of points. Furthermore, it was observed a vibration peak located at 16.71 Hz, that should be related to the wear process.